Development and Deployment of Quadcopter in Silos’ Inspection and Surveillance - Edeh, J. C.; Nwadinobi, C. P.; Obetta, E. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Efficient and routine inspection/surveillance of agricultural installations is a panacea that guarantees structural integrity and healthy storage of grains. Conventional methods of silo inspection are tedious, time-consuming, costly, disruptive and with attendant safety concerns. A quad copter comprising four Electronic Speed Controller (ESC), four Brushless DC motors, a motion camera, a flight controller unit, a battery and an off board remote controller was designed,   developed and evaluated for silos’ facility inspections. The system is powered by 11.4V LiPo (Lithium polymer) fitted on-board of the quad copter, a digital camera and a 12V remote controller for off-board control (yaw, pitch and roll), with an entire system weight of 3.62kg. Apt deployment of such unmanned aerial vehicle in routine facility integrity inspection eliminated the high risk and loss of man hour associated with contemporary techniques. The result of its performance test indicated that the system has maximum attainable speed of 10km/h and maximum height/range of 150 m for over all 10 minutes of flight time. Also, the threshold speed for each rotor was found to be 1030 rpm and an average speed of 0.5km/h needed during inspection of silos to avoid blurred images from the camera was achieved. Comparative analysis of the design with the conventional method revealed that the developed quad copter was cost and time effective, convenient, risk free thus recommended for full scale deployment for inspection/surveillance in silo installations.